2014
DOI: 10.1021/am4058937
|View full text |Cite
|
Sign up to set email alerts
|

Band Engineered Epitaxial 3D GaN-InGaN Core–Shell Rod Arrays as an Advanced Photoanode for Visible-Light-Driven Water Splitting

Abstract: 3D single-crystalline, well-aligned GaN-InGaN rod arrays are fabricated by selective area growth (SAG) metal-organic vapor phase epitaxy (MOVPE) for visible-light water splitting. Epitaxial InGaN layer grows successfully on 3D GaN rods to minimize defects within the GaN-InGaN heterojunctions. The indium concentration (In ∼ 0.30 ± 0.04) is rather homogeneous in InGaN shells along the radial and longitudinal directions. The growing strategy allows us to tune the band gap of the InGaN layer in order to match the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
60
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 31 publications
0
60
1
Order By: Relevance
“…In comparison to 2D films, 3D nanorods with subwavelength-scale induce the light-trapping effect [1821]. When the light is incident on the surface of 3D nanorods, the photons will be reflected back and forth between the nanoscale gaps resulting in an increase of light absorption (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to 2D films, 3D nanorods with subwavelength-scale induce the light-trapping effect [1821]. When the light is incident on the surface of 3D nanorods, the photons will be reflected back and forth between the nanoscale gaps resulting in an increase of light absorption (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…One facile method to tune the bandgap is changing the ratio of In:Ga in In x Ga 1-x N nanostructures, allowing for significant improvements in the ability to harvest photons from sunlight, which has demonstrated great benefits in solar-to-fuel conversion [7][8][9][10][11][12][13] . In addition, the band edges of In x Ga 1-x N straddle the reduction and oxidation potentials of water, leading to a thermodynamically favorable band structure for hydrogen and oxygen generation from water splitting 14 .…”
mentioning
confidence: 99%
“…Chakrapani et al reported an evidence of electrochemical 14 In x Ga 1−x N is a semiconductor of interest for different Fermi level pinning at the GaN surface caused by surface applications including light-emitting diodes 3,4 and biosensors. 5 In particular, InGaN has attracted a lot of attention as material 6,7 for photoelectrodes because of its large carrier mobility, high light absorption coefficient, and the ability to tune its band gap by tailoring the indium concentration. 8,9 However, the relative high overpotential of InGaN could hinder its application as photoelectrode.…”
Section: Introductionmentioning
confidence: 99%